A simplify fuzzy logic controller design based safe experimentation dynamics for pantograph-catenary system - Mohd Faisal Farhan; Nor Sakinah Abdul Shukor; Mohd Ashraf Ahmad; Mohd Helmi Suid; Mohd Riduwan Ghazali; Mohd Falfazli Mat Jusof (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Contact force between catenary and pantograph of high speed train is a crucial system to deliver power to the train. The inconsistence force between them can cause the contact wire oscillate a lot and it can damage the mechanical structure of system and produce electric arc that can reduce the performance of system. This project proposes a single-input fuzzy logic controller (SIFLC) to control the contact force between the pantograph-catenary by implement Safe Experimentation Dynamics (SED) method to tune the SIFLC parameters. The essential feature of SIFLC is that it is model-free type controller design with less pre-defined variables as compared to other existing model-based controllers. The performance of the SIFLC is analyzed in terms of input tracking of contact force of pantograph-catenary and time response specifications. A simplified model of three degree of freedom (3-DOF) pantograph-catenary system is considered. In this study, the simulation result shows that the SIFLC successfully track the given contact force with less overshoot with percentage different of peak to peak response  from actual force 2% and fast response within 5.27s